Non-small-cell lung cancer: how to manage ALK-, ROS1- and NTRK-rearranged disease - Daniele Marinelli; Marco Siringo; Giulio Metro; Biagio Ricciuti; Alain J Gelibter (BioExcel Publishing Ltd, 2022)
Oncogene addiction in non-small-cell lung cancer (NSCLC) has profound diagnostic and therapeutic implications. ALK, ROS1 and NTRK rearrangements are found in about 2-7%, 1-2% and 0.2% of unselected NSCLC samples, respectively; however, their frequency is markedly higher in younger and never-smoker patients with adenocarcinoma histology. Moreover, ALK, ROS1 and NTRK rearrangements are often mutually exclusive with other known driver alterations in NSCLC. Due to such a low frequency, diagnostic screening with accurate and inexpensive techniques such as immunohistochemistry is useful to identify positive cases; however, confirmation with fluorescent in situ hybridization or next-generation sequencing is often required due to higher specificity. In ALK-rearranged NSCLC, sequential treatment with second-generation and third-generation tyrosine kinase inhibitors leads to long-lasting disease control with most patients surviving beyond 5 years with metastatic disease. In ROS1-rearranged NSCLC, first-line treatment with crizotinib or entrectinib and subsequent treatment with lorlatinib at disease progression leads to similar results in patients with metastatic disease. NTRK1-3 fusions are extremely rare in unselected NSCLC. However, treatment with TRK inhibitors yields high response rates and durable disease control in most patients; diagnostic screening through multigene DNA/ RNA-based next-generation sequencing testing is therefore crucial to identify positive cases. This article is part of the Treatment of advanced non-small-cell lung cancer: one size does not fit all Special Issue: https://www.drugsincontext.com/special_issues/treatment-of-advanced-non-small-cell-lung-cancer-one-size-does-not-fit-all/